La lectura fácil: una apuesta de valor para las organizaciones - Pérez García, Jorge M.; López de la Cruz, Laura (Revista Española de Discapacidad, 2015)
Pérez, J.M y López, L. (2015): “La lectura fácil: una apuesta de valor para las organizaciones”, Revista Española de Discapacidad, 3 (1): 187-192.